2009
DOI: 10.1239/jap/1253279849
|View full text |Cite
|
Sign up to set email alerts
|

On Approximations of Small Jumps of Subordinators with Particular Emphasis on a Dickman-Type Limit

Abstract: Let X be a pure-jump subordinator (i.e. nondecreasing Lévy process with no drift) with infinite Lévy measure, let Xε be the sum of jumps not exceeding ε, and let µ(ε)=E[Xε(1)]. We study the question of weak convergence of Xε/µ(ε) as ε ↓0, in terms of the limit behavior of µ(ε)/ε. The most interesting case reduces to the weak convergence of Xε/ε to a subordinator whose marginals are generalized Dickman distributions; we give some necessary and sufficient conditions for this to hold. For a certain significant cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A thorough characterization of the class of pure-jump subordinatorsX such that X ε /ε converges weakly to X c as ε → 0 is provided by the author in [4]. It turns out [4] that the Dickman limit plays a central role in the context of approximating small jumps of subordinators.…”
Section: Remark 41mentioning
confidence: 99%
See 1 more Smart Citation
“…A thorough characterization of the class of pure-jump subordinatorsX such that X ε /ε converges weakly to X c as ε → 0 is provided by the author in [4]. It turns out [4] that the Dickman limit plays a central role in the context of approximating small jumps of subordinators.…”
Section: Remark 41mentioning
confidence: 99%
“…Moreover, since ε is assumed to be small and since the above series converges rapidly (depending, of course, on cT ), it is clear that we may truncate the series at some moderate number of terms. As for the CPPX ε , it has rate ∞ ε ρ(x) dx, which is asymptotically c log(1/ε) as ε → 0 (this is a particular case of a proposition in [4]), and is, hence, relatively small in general. This is very advantageous from a computational point of view.…”
Section: Remark 41mentioning
confidence: 99%
“…More precisely, the Brownian motion W can be approximated by an appropriate renormalization of the compensated sum of small jumps of a given Lévy process, see Proposition 3.5 below. In the same spirit we mention the work [8] which completes, in some sense the previous one, where it is shown that the process {t, t ∈ [0, 1]} is a weak limit of a renormalized (in an appropriate sense) sum of small jumps of classes of subordinator. We note that the family {X…”
Section: Mt S αmentioning
confidence: 70%
“…Condition (8) means that the corresponding Lévy process has finite variation paths. The characteristic exponent Ψ Λ T S α is given by…”
Section: Lévy Processes With Finite Variation Pathsmentioning
confidence: 99%
See 1 more Smart Citation